Acute Fatty Liver of Pregnancy: A Life Threatening Condition - Sitaula, Sarita; Agrawal, Ajay; Thakur, Achala; Manandhar, Tara; Thapa, Babauram Dixit; Dhamala, Jibanath (Nepal Journal of Obstetrics and Gynaecology, 2020)
Acute Fatty Liver of Pregnancy (AFLP) is a rare but catastrophic disease affecting women in pregnancy. It usually occurs in the third trimester or post-partum period. Delay in diagnosis is associated with morbid complications with high morbidity and mortality. We report a case of 24 years old female at 38 weeks period of gestation who presented with jaundice, vomiting for 3 days and deranged liver function test. She was diagnosed as acute fatty liver of pregnancy and was delivered by instrumental delivery but required cesarean hysterectomy due to postpartum hemorrhage. She started improving with supportive care and discharged after 4 weeks of hospital stay. Key words: AFLP, Hysterectomy, Postpartum hemorrhage